ANALYSIS OF PATERNALISTIC LEADERSHIP IN IMPROVING COOPERATION BETWEEN STAKEHOLDERS AND COMMUNITY SERVICES IN SOUTH KABAENA DISTRICT - Hidayat, Syamsul; Razak, Abdul; Supriaddin, Nofal (Penelitian dan Pengembangan Ilmu, 2024)
This research aims at paternalistic leadership in improving cooperation between stakeholders and community services in South Kabaena District. The benefit of this study is to find out the application of the theory and additional reference sources for human resource management theory. In addition, this research is expected to be useful as additional knowledge and reference materials as well as considerations for further research. It is hoped that it can provide input and add sources of thought to find out the behavior of paternalistic leadership in South Kabaena District. This study uses a descriptive qualitative method. Data was collected by observation, interview . The subjects of the study are employees of the board of directors or editors-in-chief who are considered to have the intensity of interaction. The results of this study describe the leadership style applied by South Kabaena District, namely the Paternalistic leadership style with three types, including: (1) Benevolent Leadership, (2) Morale Leadership, and (3) Authoritarian Leadership. Meanwhile, the implications of implementing a transformational style include: (1) helping employees outside of their work, (2) providing solutions to every problem that arises, (3) motivating their members to work hard to achieve the company's goals, (4) controlling the work of staff as previously planned, and (5) leaders rewarding outstanding employees by giving them appreciation. The results of the research can be suggested, namely in terms of references that may still be few, so that these limitations and shortcomings can be understood by readers and subsequent researchers to be able to be further researched, and with a wider scope and in a paternalistic leadership style, of course, a leader figure who is able to stimulate the creativity of his subordinates is needed. The low leadership in showing the leader's stance in working as well as the lack of leadership in attracting the attention of subordinates and the inability of the leadership to stimulate their subordinates can cause lethargy in working so this can be addressed by improving the way the leadership communicates with his subordinates.